Prediction Optimal Classification of Business Phases - Claus Weihs; Karsten Luebke (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
Linear Discriminant Analysis (LDA) performs well for classifica- tion of business phases – even though the premises of an LDA are not met. As the variables are highly correlated there are numerical as well as interpretational shortcomings. By transforming the classification problem to a regression setting both problems can be addressed by a computer-intensive prediction oriented method which also improves the classification performance.
Keywords: 519; Konjunktur; Zeitreihenanalyse; Diskriminanzanalyse; Clusteranalyse; Theorie